Destruction of antimicrobial contaminants in water and waste sludge with chemical oxidation processes - Öncü, Nalan Bilgin. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2013., 2013)
Destruction of antimicrobial contamination in both water and sewage sludge was investigated in the thesis. In the first part of the study, the effectiveness of three oxidation processes –chlorination, ozonation, and heterogeneous photocatalysis– on the destruction of a resistance carrier bacterial plasmid DNA isolated from E. Coli were compared and the relative superiority of ozonation or heterogeneous photocatalysis over conventional chlorination was demonstrated. Although the nano-fiber-TiO2 that was prepared in the study did not provide better plasmid DNA destruction compared to commercial TiO2-P25, the material is promising for facilitated catalyst separation from the treated water. In the second part of the study, simultaneous degradation of two model antibiotics, ciprofloxacin (CIP) and oxytetracycline (OTC) in secondary sewage sludge, was investigated by the application of (i) ozonation, (ii) hydrogen peroxide oxidation assisted with microwave irradiation (MW/H2O2), iii) persulfate oxidation assisted with microwave irradiation (MW/S2O8 2-), and (iv) persulfate oxidation activated with ferrous iron and conventional heating (Fe2+/heat/S2O8 2-). While under appropriate conditions all of the processes provided >95% antibiotic degradation along with sludge solubilization, they offer different benefits for waste sludge treatment. Ozonation was found to be more effective to treat the sludge with low content of total solid (TS=2.5 g/L), while the desorption of the antibiotics was required to achieve high rate of degradation at high solid content (10 g/L) of the sludge. On the other hand, owing to the desorption ability of MW in the MW/H2O2 and MW/S2O8 2- processes, and owing to the complexation of the antibiotics with iron in the Fe2+/heat/S2O8 2- process, concurrent antibiotic desorption and degradation was achieved in sludge with high TS (10 g/L). MW/S2O8 2- provided exceptional metal solubilization, considerably enhanced sludge filterability within the shortest treatment time. Along with considerable metal solubilization, the Fe2+/heat/S2O8 2- process resulted in phosphorus precipitation, which can potentially increase the fertilizer value of the sludge.
Keywords: Sewage -- Purification -- Activated sludge process.; Water chemistry.